Does College Location Affect the Location Choice of New College Graduates? Evidence from China - Mian Huang; Chunbing Xing; Xiaoyong Cui (Institute of Labor Economics (IZA), 2019)
Based on a representative survey of new college graduates in China, we examine the impact of college location on their location choice upon graduation. We use a discrete choice model and the BLP method to solve the endogeneity problem of housing cost and to estimate the unobservable location features. Furthermore, we allow for different distributions of city preference for graduates studying in different regions to address the self-selection problem of college location. Empirical results show that the graduates are significantly more likely to stay in where they attended college, to return to their hometown, and to avoid cities with high housing costs. Simulation exercise shows that the impact of college location on migration varies considerably across cities, and there is significant heterogeneity for students from universities of different tiers and from rural vs. urban areas. Reduced form evidence suggests that internship in the local labor market plays an important role in raising the probability of staying. College education increased the students' interaction with the local economy and reduced the costs of job search.
Keywords: J13; J16; J61; J24; 330; higher education; regional development; location choice; human capital